An investigation of a suitable change management strategy to ensure the adoption of a developmental culture by the workforce : the case of Theewaterskloof Municipality - Nel-Gagiano, Zanné (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.